HUBUNGAN PENGETAHUAN PERAWAT TENTANG KEGAWATDARURATAN DENGAN PELAKSANAAN TRIAGE PADA PASIEN GAWAT DARURAT DI UGD RUMAH SAKIT KEBONJATI BANDUNG - Tiarmaida Sitio; Yunita Sarah Nadeak; Andi sukandi (LPPM Akper Kebonjati, 2023)
A hospital is a form of health facility, whether organized by the government or the community, which functions to provide basic health services or referral health services or also support health services. A hospital is a form of health facility, whether organized by the government or the community, which functions to provide basic health services or referral health services or also support health services.